ANALISIS DISPOSISI MATEMATIS DAN KEMAMPUAN KOMUNIKASI SISWA KELAS XI MAN I KOTA CIREBON MELALUI PENERAPAN MODEL RECIPROCAL TEACHING - Sumliyah Sumliyah; Rifqi Hidayat; Nur Fazrin (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2017)
The research is based on the law of comunacition mathematical and mathematical disposition andthe less of the students’s activation in learning process. The research objective is to know theimprovement of ccomunication mathematical and mathematical disposition which the learningprocess used is Reciprocal Teaching learning model with conventional learning. The research isQuasi Experimental research.The research design is used Nonequivalent Control Group Design andsample collection technique is Sampling Purposive .The population in the research is the students ofclass XIth MAN I Kota Cirebon, academic year 2017/2018. The sample of the research is the XIthqraders 39 th student class XIth A is classes eksperimental and 39 th student class XIth B is classescontrol. Based on the result of the difference of the average of post-test using the test ofIndependent Sample T-Test equals sig (2 tailed) score 0,000 < 0,05 means H0 rejected. And then thedifference of the average using of N-gain using the test of Independent Sample t-test equals sigscore (1 tiled) 0,0005 < 0,05 means H0 rejected. On the other hard, based on the result ofquestionnaire using the test of Mann Whitney U-Test eguals Asymp. Sig(2 tailed) 0,000 < 0,5means H0 rejected. The research result shows that: (1) Comunication mathematical which is usingReciprocal Teaching learning model is better than the students who are learning by conventionallearning process. (2) The improvement of communication mathematical which is using ReciprocalTeaching learning model is better than the students who are learning by conventional learningprocess. (3) The improvement of mathematical disposition which is using Reciprocal Teachinglearning model is better than the students who are learning by conventional learning process.Key Words: Mathematical Disposition, Comunication Mathematical, Reciprocal Teaching.